Bond strength comparison among 10-MDP-containing and non-10-MDP-containing adhesives in different degrees of dental fluorosis = Comparación de fuerza de unión entre adhesivos que contienen y no contienen 10-MDP en diferentes grados de fluorosis dental - Solís Martínez, Luis Javier; Valles Flores, Karla Yareli; Vargas Chávez, Nohé; Almeda Ojeda, Oscar Eduardo; Barajas Pérez, Víctor Hiram (2023)
Dental fluorosis can cause changes in the enamel surface, conditioning its functionality and esthetics. The application of dental adhesives is a treatment option; however, their use on fluorotic teeth can result in limitations. The aim of this study was to compare the shear bond strength of two different adhesives, one with 10-MDP and one without 10-MDP, in different degrees of dental fluorosis.This is an in vitro study on dental enamel samples, a total of 180 samples with the inclusion criteria were treated, randomly divided into two groups of 90, according to the type of dental adhesive, where each group was again divided into three groups of 30 samples, representing different degrees of dental fluorosis according to the Thylstrup-Fejerskov index (Group I: TF1 and TF2; Group II: TF3; Group III: TF4). Normality tests, two-factor ANOVA, and post-hoc tests were used to determine differences between the groups, with a significance level of 95%. As results, a statistically significant difference was shown between the use of dental adhesive with 10-MDP and the three groups of dental fluorosis (p=0.011), in addition, a Tukey post-hoc test on the groups treated with 10-MDP adhesive revealed a statistically significant difference between group I versus group II, and group I versus group III, (p=<0.05). It is concluded that the use of adhesive systems with 10-MDP presents a better shear bond strength on enamel with dental fluorosis grades I and II in the Thylstrup-Fejerskov index.
La fluorosis dental puede ocasionar cambios en la superficie del esmalte, condicionando su funcionalidad y estética, la aplicación de adhesivos dentales es una opción de tratamiento, sin embargo, su uso en dientes fluoroticos puede resultar en limitaciones. El objetivo de este estudio consistió en comparar la fuerza de adhesión a la cizalladura de dos diferentes adhesivos, uno con 10-MDP y otro sin 10-MDP, en diferentes grados de fluorosis dental. Se trata de un estudio in vitro en muestras de esmalte dental, un total de 180 muestras con los criterios de inclusión fueron tratadas, aleatoriamente divididas en dos grupos de 90, de acuerdo al tipo de adhesivo dental, donde cada grupo fue dividido nuevamente en tres grupos de 30 muestras, representando diferentes grados de fluorosis dental según el índice de Thylstrup-Fejerskov (Grupo I: TF1 y TF2; Grupo II: TF3; Grupo III: TF4). Para determinar diferencias entre los grupos se utilizaron pruebas de normalidad, ANOVA de dos factores, y pruebas post-hoc, con un nivel de significancia de 95%. Como resultados, se mostró una diferencia estadísticamente significativa entre el uso de adhesivo dental con 10-MDP y los tres grupos de fluorosis dental (p=0.011), además, una prueba post hoc de Tukey sobre los grupos tratados con adhesivo 10-MDP revelaron una diferencia estadísticamente significativa entre el grupo I frente al grupo II, y el grupo I frente al grupo III, (p=<0.05) Se concluye que el uso de sistemas adhesivos con 10-MDP presentan una mejor resistencia de adhesión al cizallamiento en esmalte con grados de fluorosis dental I y II en el índice de Thylstrup-Fejerskov.
En revista Odóvtos, vol. 25, no.1 (enero-abril 2023)
Descripción basada en el contenido visto el 12 de diciembre, 2024
También disponible en formato HTML y EPUB